2021
DOI: 10.1016/j.jpra.2021.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Digital art - a useful tool for medical professionals to create medical illustrations

Abstract: Illustrations are routinely used in medicine for teaching, communication, record keeping, research and publication purposes. Many medical professionals including the author prefer to create their own medical illustrations for use in presentations and publications. With the advent of digital media, it has become easier to create good quality illustrations even for those with limited artistic skills including the author. This article describes the author's experience with creating medical illustrations using dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…While the importance of preoperative treatment planning has been widely recognized, a detailed description of intraoperative findings using easy-to-understand illustrations also has pivotal roles and may contribute to improving treatment quality. Furthermore, the role of medical illustration in surgical records is to record surgical information, improve one’s surgical skills, and educate young doctors [ 1 , 2 ]. However, we believe it is challenging for beginners to create medical illustrations from a blank sheet of paper.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the importance of preoperative treatment planning has been widely recognized, a detailed description of intraoperative findings using easy-to-understand illustrations also has pivotal roles and may contribute to improving treatment quality. Furthermore, the role of medical illustration in surgical records is to record surgical information, improve one’s surgical skills, and educate young doctors [ 1 , 2 ]. However, we believe it is challenging for beginners to create medical illustrations from a blank sheet of paper.…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe it is challenging for beginners to create medical illustrations from a blank sheet of paper. The computer-assisted illustration technique not only saves time but also provides accurate and easy-to-understand medical illustrations [ 2 ]. The previous reports include methods of converting radiologic images to line art using photo editing software and digitization of hand drawings [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Good medical illustrations can improve the quality of a research paper by efficiently conveying content to the readers [ 8 , 9 ]. When reviewing the articles published in the Korean Journal of Pain in 2023 (including review articles, clinical research articles, and experimental research articles only), illustrations, except graphs or charts, were found in 7.9% of the articles (3 out of 38).…”
Section: To the Editormentioning
confidence: 99%
“…The characteristic or fundamental policy of education is to face reality directly. If these are lost, vocational education will deviate from its course [5][6]. Due to the lack of industry research in many colleges and universities, and some teachers do not pay attention to professional development, the technology taught is outdated and cannot adapt to the ever-changing changes in science and technology [7][8].…”
Section: Introductionmentioning
confidence: 99%